Shattered : a novel - Jeremiah, David, 1941-; O'Neal, Sam, 1981- (The vanished series, 2026)
Two years have passed since millions across the globe disappeared in a heartbeat including John "Haggs" Haggerty's own family. Haggs, a military expert in pandemics, warned his agency of growing patterns in deadly epidemics and other threats to security. Then the "Great Disappearance" and the nuclear destruction of the US changed everything. Now he is invited to join the powerful Trident Group, led by the wealthy Matthias Vilks. Inside Trident, Haggs sees patterns that suggest a coordinated plan to control economies and governments. He is not alone. Israeli tech expert, Saul Katz, saw his colleague disappear before his eyes. Now the Israeli government confiscates his life's work, a defense system for Israel. Li Fan, monitoring seismic anomalies, sees terrifying signals in the earth's activity, but no one will listen to her warnings. As the disturbing pieces fall in place, governments fall, and John and his best friend's daughter, Abigail, begin to see those prophecies from scripture come to life--Israel is in danger, natural disasters rake the planet, and world leaders bow to one powerful man. The signs are clear: the end times are no longer approaching--they have begun.